(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The archaeological excavation conducted by the University of Milan at the site of Gortys (Crete) in 2010 on the northern side of the “Terme Milano” has revealed a new room of the building, called G, characterized by a pebbles paving. On the paving a little limekiln was discoreved, testifying the last phase of life of the abandoned building.